2007
DOI: 10.1136/oem.2007.033167
|View full text |Cite
|
Sign up to set email alerts
|

An occupational health intervention programme for workers at high risk for sickness absence. Cost effectiveness analysis based on a randomised controlled trial

Abstract: Objectives:To determine whether, from a healthcare perspective, a specific occupational health intervention is cost effective in reducing sickness absence when compared with usual care in occupational health in workers with high risk of sickness absence.Methods:Economic evaluation alongside a randomised controlled trial. 418 workers with high risk of sickness absence from one corporation were randomised to intervention (n = 209) or to usual care (n = 209). The subjects in the intervention group were invited to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 14 publications
(16 reference statements)
2
41
0
Order By: Relevance
“…Alternatively, when researchers want to select high-risk individuals (e.g., for randomised-controlled trials or interventions) then cut-off risks [40 % should be chosen. In this regard, it is important to notice that Taimela et al [33] found that preventive consultations aimed at reducing SA were cost-effective only in high-risk workers, not in those at moderate or low risk of SA.…”
Section: Practical Implicationsmentioning
confidence: 95%
“…Alternatively, when researchers want to select high-risk individuals (e.g., for randomised-controlled trials or interventions) then cut-off risks [40 % should be chosen. In this regard, it is important to notice that Taimela et al [33] found that preventive consultations aimed at reducing SA were cost-effective only in high-risk workers, not in those at moderate or low risk of SA.…”
Section: Practical Implicationsmentioning
confidence: 95%
“…Furthermore, interventions may alter the prognosis and consequences of LTSA. Taimela et al (14) showed that preventive consultations reduced sickness absence, although such consultations were cost-effective only among high-risk workers (15). The cost-effectivity of preventive consultations may increase when only high-risk workers are referred, which accentuates the need to screen for risk of LTSA.…”
mentioning
confidence: 99%
“…We would however have to go back to the individual patient data to be able to take this into account. ICER are difficult to interpret especially when the intervention saves more cost and is more effective than the alternative as in the case of Taimela et al (7) and as discussed by Drummond (4). The problem is that the highest combination of cost saving and effect gain does not necessarily translate into the best ICER.…”
Section: Discussionmentioning
confidence: 99%
“…Taimela et al (7) evaluated an occupational health intervention program for workers at high risk for sickness absence. A health risk appraisal questionnaire, sent to 3115 employees of a Finnish company, identified 418 employees at high risk for sickness absence who were willing to participate in the study.…”
Section: The Original Studies and Their Contextmentioning
confidence: 99%
See 1 more Smart Citation